Use of Word Racing Game (سباق الكلمات) for Nahwu Learning at Madrasah Ibtidaiyyah Nurul Amal Mojokerto - udin, Amzal; A, Fairuzah; Muassomah, Muassomah; Muballigh, Ahmad (Armala, 2023)
This study aims to describe the process of applying or using word races and their advantages and disadvantages in Nahwu learning, especially in the material of Isim Mudzakkar and Muannats at Madrasah Nurul Amal Mojokerto. This research was conducted with field research with a descriptive qualitative approach. With interactive data analysis techniques. Based on the results of the study, the use of this learning word race game will entirely be student-centered or known as Student Centered Learning (SCL). increase student motivation to learn. Its interesting principle is to learn while playing and cultivate a love for the Arabic language. Because the use of Gamification in language learning proves that the use of Gamification for foreign language learning has a positive impact, both in increasing learning motivation and achieving learning objectives. These games provide opportunities for students to actively engage, understand concepts better, and improve their Arabic skills. The disadvantages of this game are time pressure which has implications for one of the children's learning motivation, children's interests outside school, and the adjustment of children's learning activities to children's needs.